Hypergranular precursor B-cell acute lymphoblastic leukemia in a 16-year-old boy - Tembhare Prashant; Subramanian P; Sehgal Kunal; Yajamanam Badrinath; Kumar Ashok; Gujral Sumeet (Wolters Kluwer Medknow Publications, 2009)
Presence of cytoplasmic granules in the blasts is a well known feature of myeloid leukemia. ALL presenting with the numerous cytoplasmic granules in blasts is a rarity and may be misdiagnosed as acute myeloid leukemia. We describe a rare case of hypergranular precursor B-cell acute lymphoblastic leukemia (ALL) in an adolescent male expressing CD10, CD19, CytoCD22, CD34, as well as CD13 and CD117. The blasts were cytochemically negative for myeloperoxidase (MPO), and acid phosphatase (ACP) but were positive for non-specific esterase (NSE). In centers where immunophenotypic panel is usually decided on the basis of morphology with limited antibodies may result in an erroneous typing of such rare diseases. Hence it is important to be aware of this rare entity and to confirm the lineage of acute leukemia by using a comprehensive panel of antibodies for immunophenotypic analysis.